Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

On-ice vibroseis and snowstreamer systems for geoscientific research - Eisen, Olaf; Hofstede, Coen; Diez, Anja; Kristoffersen, Yngve; Lambrecht, Astrid; Mayer, Christoph; Blenkner, Rick; Hilmarsson, Sverrir (Recent Advance in Polar Seismology: Global Impact of the International Polar Year, 2015)
We present implementations of vibroseis system configurations with a snowstreamer for over-ice long-distance seismic traverses (>100 km). The configurations have been evaluated in Antarctica on ice sheet and ice shelf areas in the period 2010–2014. We discuss results of two different vibroseis sources: Failing Y-1100 on skis with a peak force of 120 kN in the frequency range 10–110 Hz; IVI EnviroVibe with a nominal peak force of 66 kN in the nominal frequency range 10–300 Hz. All measurements used a well-established 60 channel 1.5 km snowstreamer for the recording. Employed forces during sweeps were limited to less than 80% of the peak force. Maximum sweep frequencies, with a typical duration of 10 s, were 100 and 250 Hz for the Failing and EnviroVibe, respectively. Three different concepts for source movement were employed: the Failing vibrator was mounted with wheels on skis and pulled by a Pistenbully snow tractor. The EnviroVibe was operated self-propelled on Mattracks on the Antarctic plateau. This lead to difficulties in soft snow. For later implementations the EnviroVibe with tracks was put on a polyethylene (PE) sled. The sled had a hole in the center to lower the vibrator baseplate directly onto the snow surface. With the latter setup, data production varied between 20 km/day for 6-fold and 40 km/day for single fold for 9 h/day of measurements. The combination of tracks with the PE-sled was especially advantageous on hard and rough surfaces because of the flexibility of each component and the relatively lose mounting. The systems presented here are suitable to obtain data of subglacial and sub-seabed sediment layers and englacial layering in comparable quality as obtained from marine geophysics and land-based explosive surveys. The large offset aperture of the streamer overcomes limitations of radar systems for imaging of steep along-track subglacial topography. With joint international scientific and logistic efforts, large-scale mapping of Antarctica's and Greenland's subglacial geology, ice-shelf cavity geometries and sea-bed strata, as well as englacial structures can be achieved.
Keywords: Dronning Maud Land; isshelf; seismologi; teknologi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Keywords: Antarktis; glasiologi; seismologi

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi